Implementasi E-Government di Tingkat Desa: Analisis Ketersediaan dan Kemutakhiran Konten Informasi Publik di Desa Soreang Kab Takalar: e-government, website desa, ketersediaan informasi, kemutakhiran konten, Desa Soreang - Muh Fadli Fauzi Sahlan; Supriadi Syam; Sahabuddin Sahabuddin; Abdillah SAS (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2026)
The implementation of e-government at the village level is crucial for enhancing public service transparency and accountability. This study aims to evaluate the implementation of e-government in Soreang Village, Takalar Regency, by analyzing the availability and up-to-dateness of public information content on the village's official website. Using a descriptive qualitative approach, data were collected through digital observation (web-tracing), documentation studies of Permendesa No. 13 of 2025 and Permen Komdigi No. 5 of 2025, and structured interviews with the website administrator. The results indicate that the website meets 77.8% of the mandatory menu requirements, with weaknesses in the absence of APBDes realization reports and interactive public assistance features. Content updates are uneven; dynamic content such as news is regularly updated, while static content such as demographic data and organizational structure lags. This study concludes that e-government implementation in Soreang Village is still at the publish-oriented stage, focusing on one-way information publication rather than interactive service. Challenges include limited human resource capacity and bureaucratic data fragmentation. Holistic interventions are recommended, including continuous technical training, integrated information systems, and multi-level collaboration to achieve adaptive and accountable digital governance.